Secret Analysis of Management Strengthening Strategy to Improve the Quality and Efficiency of Dance Studios - Mulyani, Sri; hartono; Purnomo, Sucipto Hadi (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2025)
This article analyzes effective management strengthening strategies to enhance the quality and efficiency of dance studios. Using qualitative research methods, including case studies and SWOT analysis, this study identifies key factors influencing studio quality and efficiency. The results indicate that strategic planning, human resource management, operational management, financial management, and marketing are crucial for improving dance studio quality and efficiency. Recommendations include developing strategic plans, optimizing resource management, and enhancing management capabilities. This article contributes to the development of effective and efficient dance studio management.